A Review of Christians Participation in Nigerian Politics from 2011-2023 - Okoh, Blessing Uenosen; Majimre, Simon Jeji (NIU Journal of Humanities, 2024)
This paper sets to examine the challenges facing Christians Participation in Nigeria’s political theatre of Fourth Republic. The study relied on empirical data and documented related materials for qualitative analysis. The study established that politics remains the avenue where societies choose leaders to govern and make policy for the popular majority of the masses in a democratic setting. Nigeria’s current Fourth Republic seems to be the longest in the history of the nation having spent over twenty years of steady democratic rule. However, what informed this study is the level of Christian Participation in the politics of Fourth Republic that has been adjudged to be below expectation by the right-thinking citizens in the nation. For example, 2011, 2015, 2019 and 2023 general elections results released by Independent National Electoral Commission indicates voter apathy in a Christian dominated states across the country. While Christians are often first to cry foul of any government policy that is perceived to be anti-Christian, their participation however, remains below expectation.  Hence the need to look at the challenges facing Christian Participation with aim of proffering solution to the challenges. Therefore, the study is not an attempt to polarize the nation’s politics base on religious line but to encourage active Participation of genuine Christians for better representation and national development. The study concludes that for Nigerian project to succeed, Christians must be involved, not passively but actively. Christians are advised to be on the driving seat in bringing about the desired change in the country. This is because Christians are better equipped, placed and specially endowed by God through Jesus Christ to be different. Recommendations were given among which includes the need for awareness creation and mentorship by those Christians who are already in the theatre of Politics. Keywords: Christians, Participation, Nigerian and Politics